2018
DOI: 10.3329/nimcj.v9i1.35924
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of blood gas status with the mortality of neonates admitted in ICU

Abstract: Background : Blood gas abnormalities are frequently encountered in sick neonates admitted in ICU. They contribute significantly to mortality. Therefore, blood gas status is a helpful indicator of the condition of sick neonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In study by Yusuf et al stated that Metabolic acidosis with base excess <5mmol/l is frequently seen in non-survivors and in critically ill patients it serves as a powerful marker for poor prognosis. 9 In the present study it was also found that patient who presented with lethargy had increase level of base excess with a p value of 0.…”
Section: Discussionsupporting
confidence: 70%
“…In study by Yusuf et al stated that Metabolic acidosis with base excess <5mmol/l is frequently seen in non-survivors and in critically ill patients it serves as a powerful marker for poor prognosis. 9 In the present study it was also found that patient who presented with lethargy had increase level of base excess with a p value of 0.…”
Section: Discussionsupporting
confidence: 70%
“…The study by M. Mohammad Yusuf showed that: the mortality group had a lower blood pH (7.3±0. 19) than the alive group (7.36±0.1); and the BE of the mortality group was lower (-10.74±15.89 mmol/L) than the live group (-4.3±6.88 mmol/L) [14].…”
Section: Discussionmentioning
confidence: 78%